2020
DOI: 10.1021/acs.jpclett.0c00689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Bonding between Ions of Like Charge on the Boundary Layer Friction of Hydroxy-Functionalized Ionic Liquids

Abstract: Atomic force microscopy has been used to measure the lubricity of a series of ionic liquids (ILs) at mica surfaces in the boundary friction regime. A previously unreported cation bilayer structure is detected at the IL−mica interface due to the formation of H-bonds between the hydroxy-functionalized cations [(cc) H-bonds], which enhances the ordering of the ions in the boundary layer and improves the lubrication. The strength of the cation bilayer structure is controlled by altering the strength of (c-c) H-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Interactions due to hydrogen bonds between ions of the same charge can control the boundary laver friction at an RTIL‐mica interface. Therefore, it can have an impact on various applications, electrochemistry [7,38,39] and physical properties like enthalpies. Especially the enthalpy of vaporization is influenced by hydrogen bonds in hydroxyl‐functionalized RTILs [40] …”
Section: Resultsmentioning
confidence: 99%
“…Interactions due to hydrogen bonds between ions of the same charge can control the boundary laver friction at an RTIL‐mica interface. Therefore, it can have an impact on various applications, electrochemistry [7,38,39] and physical properties like enthalpies. Especially the enthalpy of vaporization is influenced by hydrogen bonds in hydroxyl‐functionalized RTILs [40] …”
Section: Resultsmentioning
confidence: 99%
“…Until then, like-charge attraction in "real systems" had been reported mainly for large-scale structures, assemblies, or stabilizing frameworks [13][14][15][16][17][18][19][20][21]. Overall attractive interaction between the "likes" in liquids and solutions required screening effects caused by neighboring counterions, polar molecules, or generally favorable dielectric environments [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Our attempts aimed not only to detect but to control like-charge attraction by varying molecular parameters.…”
Section: Of 22mentioning
confidence: 99%
“…Obviously, hydrogen bonds between ions of like charge can be stronger than those between ions of opposite charge despite the repulsion in the first interaction and the attractive Coulomb interaction in the latter case. Recently, we showed by means of molecular dynamics (MD) simulations that the hydrogen bonding lifetimes of the (c + -c + ) H-bonds can be longer than those of the (c + -a − ) H-bonds for alkyl chain length n = 4-5, reflecting the different interaction strengths in both types of hydrogen bonds, as indicated by IR and NMR spectroscopy [32][33][34][35]. However, the populations derived from neutron diffraction data showed that only less than 20% of all hydrogen bonds refer to (c + -c + ) bound clusters at room temperature.…”
Section: Of 22mentioning
confidence: 99%
See 1 more Smart Citation
“…increasing their melting point and viscosity, reducing their conductivity, inhibiting crystallization under supercooled conditions and changing the interfacial nanostructures of ILs. 25,[33][34][35] However, to the best of our knowledge, no research on the HBs between the anions of ILs has been reported so far.…”
Section: Introductionmentioning
confidence: 99%